Enhancing Career Decision Status of Socioeconomically Disadvantaged Students Through Learning Engagement: Perspective of SOR Model - Peng, Michael Yao-Ping; Yue, Xiaoyao (Frontiers in Psychology, 2022)
Higher education plays the role of cultivating talents in national development and meets the talent sources needed by the development of the state, industries and enterprises. Besides, for students, higher education can provide stimuli to improve the development of family and personal career. Especially for socioeconomically disadvantaged Students, higher education means the main factor for turning over the Socio- Economic Status. Universities endow students with abundant employment skills，so as to make them more confident in contending with the challenges in the job market. However, innate pessimism or negative attitudes and cognition may exist in socioeconomically disadvantaged Students, thereby providing effective learning context to improve their learning engagement. This study explores the influence on students’ career decision status from deep approach to learning, problem-based learning, self-efficacy and employability. A total of 627 valid questionnaires are collected in this study. PLS-SEM was adopted to verify the structural relationship in data analysis via SmartPLS. The results indicate that deep approach to learning and problem-based learning have significant impacts on students' self-efficacy and employability; self-efficacy has significant impacts on employability and career decision status; employability has significant impact on career decision status; and that self-efficacy and employability play significant mediating roles in the research framework.